Effect of Oxygen and Carbon Dioxide Concentration on the Quality of Minikiwi Fruits after Storage - Tomasz Krupa (MDPI AG, 2021)
The rapid increase in the production of hardy kiwi fruit (A. arguta) since the beginning of the 21st century has required the development of new cultivation technologies and postharvest handling procedures in order to extend the supply and transport of the fruit to distant markets. Fruit storage focuses on the inhibition of ripening processes regulated by ethylene activity or respiration. Both of these are effectively regulated by appropriate concentrations of O2 and CO2 in the atmosphere surrounding the fruit. In this study, the effect of the concentration of both gases in the cold room on the physico-chemical indices of fruit quality, i.e., mass loss, firmness, soluble solids and monosaccharides content, titratable acidity and acid content, and color of the peel was evaluated. Studies have shown that high CO2 concentrations inhibit ripening processes more effectively than low O2 concentrations. Softening of berries as well as an increase in soluble solid contents was recorded during the first 4 weeks of storage in the fruit. However, the increase in monosaccharides was fairly stable throughout the study period. The increase in soluble solids content as well as the loss of acidity were more strongly determined by CO2 than O2, although the acid content in a 10% CO2 atmosphere did not change. Additionally, the fruits were greener after storage in 10% CO2, but the weakness was skin dulling and darkening. The results indicate that the use of high CO2 concentrations (5–10%) effectively inhibits ripening processes in fruit. After 12 weeks of storage, the fruit was still not suitable for direct consumption, which suggests that the storage period can be extended further.